Estudo meta-analítico sobre confiança de marca: uma análise de antecedentes, consequentes e moderadores - Rosa, Jean Carlos de Oliveira (Universidade do Vale do Rio dos Sinos, 2021)
One of the main goals of a brand is to achieve a competitive advantage, and one of the ways to accomplish this goal is to build brand trust, making its consumers take on a long-term relationship with the brand. Brand trust is a theme that has been gaining great relevance in the literature since the early 2000s. However, the results found present divergences regarding the relationships tested and effects found in the relationships between brand trust and other variables. This study aims to defragment the literature and identify the antecedents and consequences of brand trust using the meta-analysis method. Through a comprehensive systematic review, 314 quantitative studies were identified, conducted between 2001 and 2020, which produced 859 effect sizes about the relationship between brand trust and other variables used in this study. From the systematic review, seven antecedent variables and five consequent variables of brand confidence were identified, in which a high level of heterogeneity was identified. Thus, meta-regression tests were performed to identify possible moderators for the variables that presented significant relationships with a higher density of observations. The strongest antecedent relationships found were brand satisfaction, brand quality and brand image, while the main consequent relationships were brand loyalty and brand commitment. The main possible moderators found were uncertainty avoidance and country corruption, considering the countries where the research was applied. The strongest effect on brand satisfaction and brand trust’s relationship was found at higher levels of uncertainty aversion, however in the relationship between brand trust and brand loyalty the stronger effects were found in countries with lower uncertainty aversion levels. The country corruption moderator effect was found in brand satisfaction and brand trust’s relationship, presenting stronger effects when the country has lower levels of corruption. This study's academic contribution lies in the organization of what is known about brand trust. It is expected that it can serve as a guide for researchers interested in the subject. From a management perspective, the study presents the main variables that help build brand trust and the consequences of brand trust in the consumer's relationship with the brand.
Keywords: Confiança de marca; Meta-análise; Marketing; Marca; Revisão sistemática; Brand trust; Meta-analysis; Marketing; Brand; Systematic review; ACCNPQ::Ciências Sociais Aplicadas::Administração